Effect of different doses of an injectable compound of Cu, Zn and Mn on bio-productive indicators of milking cows - Noval, E.; Ramón, J.; García López, R.; Jiménez, J. (Cuban Journal of Agricultural Science, 2016)
Different doses of an injectable compound of Cu, Zn and Mn on bio-productive indicators of milking cows. Four groups were formed, with seven cows each, belonging to Siboney de Cuba (5/8 Holstein 3/8 Zebu) breed genotype, with eight months of gestation. Each group was assigned with the following treatments: A) control; B) 25 mg of Cu, 50 mg of Zn and 25 of Mn; C) 50 mg of Cu, 100 mg of Zn and 50 mg of Mn and D) 75 mg of Cu, 150 mg of Zn and 75 mg of Mn, provided every two months up to completing three applications. Serum concentrations of Cu and Zn and bio-productive indicators were evaluated. Two groups with five cows were formed: one of them received C treatment and the other, used as control, was destined to evaluate hepatic reserves of Cu, Zn and Mn. C and D treatments increased significantly (P< 0.05) serum concentrations of Cu and Zn regarding the rest of them. C treatment increased significantly (P< 0.05) the hepatic levels of Zn and Cu, and Mn (P < 0.001). Reproductive indicators were better (P<0.05) in cows that received C and D treatments, showing the highest levels of milk production (P< 0.05), after 60 d of lactation, regarding A and B groups. It can be concluded that C and D treatment were more effective to reestablish the organic levels of these microelements and favor productive and reproductive indicators of animals. Key words: copper, zinc, manganese, doses, injectable, indicator, milking cows